The position of environmental protection in the value ranking of vocational education actors - Bilčík, Alexander; Jana Bilčíková; Michal Hanák (Technium Social Sciences Journal, 2020)
The article points out the accompanying environmental consequences resulting from the development of industry, transport and increasing globalization. Subsequently, it emphasizes the necessary education of the population, education for sustainable development and raising environmental awareness. It characterizes the starting points in legislation and strategic documents of environmental policy in the field of environmental education and training in schools in the Slovak Republic. It clarifies the implementation of vocational education of students in primary and secondary schools with a focus on their environmental literacy and competencies. In it, the authors interpret the results of a survey conducted on a sample of 3070 respondents, in which they organized ten life values ??according to importance. They compare the statements of three groups of respondents - teachers, parents, and students. Subsequently, they analyse them and point out the possible causes of the identified state of the position of the value of environmental protection in vocational education in Slovak schools. In the end, they name important topics and assumptions leading to improved preparation of students for the future.